Case Service System at the Child Welfare Institution using the Case-Based Reasoning Method - Gigih, Priyandoko; Andriani , Citra; Istiadi , Istiadi; Abd Wahab , Mohd Helmy (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2020)
The Child Social Welfare Institution (LKSA) is an institution tasked with providing relief services to meet the standards of living, health, education, and the social needs of both individuals and groups. An LKSA Robbani is one of the institutions that help in handling family and child cases by National Standards for Child Care. In solving child problems, the institution must open the previous case data to determine the appropriate solution, such that the service process becomes long. Therefore, an application software is needed that can help the institution to be faster. The developed system is using the Case-Based Reasoning (CBR) Method. The advantage of this method is how to adapt the solutions of the previous case, as well as in seeking similarity in each case that the most significant similarity value is considered the most similar case. The method is very suitable for building the application. The system that was built had to do a trial before being used by the user. The trial result was carried out of the system with manual calculations using the case-based reasoning method. Furthermore, from the results of the trial, it was produced by 87.5%.